2019
DOI: 10.1002/cae.22102
|View full text |Cite
|
Sign up to set email alerts
|

A smartphone‐based augmented reality system for university students for learning digital electronics

Abstract: The fundamental concepts of electronic devices are generally taught in the initial courses of electrical and electronics engineering. For students, it is very important to grasp the basic concepts that make computers and digital systems possible. Among these concepts, boolean algebra and logic gates stand out. In this paper, a smartphone‐based augmented reality (AR) system is proposed which helps in the adequate learning of logic gate integrated circuits (ICs). The proposed system allows the automatic identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The process makes the learning process more tangible and hands-on, even for abstract content. It is envisaged that by using AR, the students would be able to better achieve learning outcomes through engagement and interactivity with the learning content [3,16,30].…”
mentioning
confidence: 99%
“…The process makes the learning process more tangible and hands-on, even for abstract content. It is envisaged that by using AR, the students would be able to better achieve learning outcomes through engagement and interactivity with the learning content [3,16,30].…”
mentioning
confidence: 99%
“…Also, usability of two design variants of the ARLE in terms of manipulability and comprehensibility was discussed HARUS is used to evaluate system usability Prit Kaur et al (2019) Electronics Engineering Laboratory equipment (CRO) AR based tabletop learning environment The findings of this study indicate that augmented reality (AR) is a suitable technology for creating interactive AR experiences for engineering education Cognitive load and learning motivation Singh et al ( 2019 ) Electronics Engineering Logic gates using AR Handheld AR device The marker less paradigm identifies the ICs and places three objects: IC identification, pins information, and logic diagram information. The AR system's overall evaluation was given a technical efficiency of 97.5 Survey questionnaire was prepared to evaluate system usability Avilés-Cruz and Villegas-Cortez ( 2019 ) Electronics Engineering Resistive electrical circuit on breadboard AR based mobile application The results of the research show that the system aids the user in comprehending and comparing the theoretical and experimental values of circuit parameters via an AR layer displayed on the smartphone User experience, perception, and perceived ease of use was evaluated Garcia-Sanjuan et al ( 2018 ) Electronics Engineering Analog and digital communication AR based mobile application Students gave feedback that hand-held device cause hindrances in robust equipment handling so it could be improved by using HMD’s Accuracy and efficiency of the system was calculated Baloch et al (2018) …”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous research papers have been presented in the literature to examine the effect of AR on learning abilities, motivation, knowledge gain, critical thinking skills, and cognition. The literature revealed that using AR-based interaction methods to teach the idea of logic gates in digital electronics has been attempted, but it involved only abstract concepts of logic gates (Avilés-Cruz & Villegas-Cortez, 2019). A mobile application was Handheld augmented reality usability scale (HARUS), Comprehensibility, manipulability Santos and Sandor (2008) proposed to provide immersive and interactive features to the users to enhance learning (Selek, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The fundamental concepts of digital electronic devices such as Boolean algebra and logic gates can be addressed using AR, which was proposed by [32] to help in the identification of seven basic logic gates: AND gate, OR gate, NOT gate, NAND gate, NOR gate, XOR gate, and XNOR gate. Ref.…”
Section: Related Workmentioning
confidence: 99%